2019
DOI: 10.1186/s12916-019-1424-4
|View full text |Cite
|
Sign up to set email alerts
|

Customized versus population birth weight charts for identification of newborns at risk of long-term adverse cardio-metabolic and respiratory outcomes: a population-based prospective cohort study

Abstract: Background Customized birth weight charts take into account physiological maternal characteristics that are known to influence fetal growth to differentiate between physiological and pathological abnormal size at birth. It is unknown whether customized birth weight charts better identify newborns at risk of long-term adverse outcomes than population birth weight charts. We aimed to examine whether birth weight classification according to customized charts is superior to population charts at ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Blood samples were obtained, transported, and stored as described in detail previously [ 16 ]. Serum concentrations of total cholesterol, triglycerides and HDL-c were measured at the Erasmus Medical Centre with enzymatic methods (Cobas 8000, Roche, Almere, the Netherlands) [ 16 , 21 , 22 ]. Levels of LDL-c, remnant cholesterol and non-HDL-c were calculated [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were obtained, transported, and stored as described in detail previously [ 16 ]. Serum concentrations of total cholesterol, triglycerides and HDL-c were measured at the Erasmus Medical Centre with enzymatic methods (Cobas 8000, Roche, Almere, the Netherlands) [ 16 , 21 , 22 ]. Levels of LDL-c, remnant cholesterol and non-HDL-c were calculated [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The influence of birthweight on developing NAFLD was investigated in nine papers. In two studies, a low birthweight and being born SGA were not significantly associated with the occurrence of NAFLD, with an OR of 1.40 (95% CI: 0.87 -2.26, P=0.17) 25 and 1.77 (95% CI: 0.88 -3.54), respectively 37 . However, rapid catch-up growth after SGA correlated with NAFLD in the study by Breij et al (with an OR of 11.7, 95% CI: 1.12 -113.3, P=0.016) 46 .…”
Section: Birth Anthropometricsmentioning
confidence: 95%
“…Different diagnostic tools were used for the diagnosis of NAFLD and/or NASH in the included studies: 6 (18.2%) studies employed biopsy 18-23 , 11 (33.3%) studies ultrasound [24][25][26][27][28][29][30][31][32][33][34] , 12 (36.4%) studies MRI 10,[35][36][37][38][39][40][41][42][43][44][45] and the remaining 4 (12.1%) studies the FLI [46][47][48][49] .…”
Section: Included Studies and Basic Characteristicsmentioning
confidence: 99%
“…This suggests our third trimester screening model may aid in the identification of newborns who are pathologically small or large for their gestational age. We did not use customized birth weight centiles for classification of abnormal size at birth as a method to distinguish potential pathological SGA and LGA newborns from constitutional SGA or LGA newborns, as previous studies have not shown strong results regarding the use of customized charts to identify SGA or LGA newborns at higher risk of mortality and adverse short-term and long-term outcomes [40,41]. A limitation of our cohort is that we do not have extensive information available on neonatal morbidity.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%